Pelatihan PELATIHAN PELAJAR KELAS XII IPA SMA MENELITI MELALUI SAYEMBARA RISET OBAT TRADISIONAL - Tukan, Gerardus Diri; Markus Taek, Maximus; Latumakulita, Gertreda; Nadut, Anggelinus; Landi Pote, Lodowik; Dewi Q. M. Bulin, Christiani; Risan Funan Lalong, Paulus (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
High school students in Indonesia, in today's development, have a final assignment before completing their senior secondary education, namely conducting scientific research, writing up research results and presenting them. General conditions show that female students still have difficulty conducting research which includes research ideas or topics, steps for conducting research and writing research results. In response to this condition, research training was created for class The method used is competition. Female students are invited to conduct research, collect data and analyze data in their respective places of residence during the holiday period. As a result of the activities obtained, as many as 35 female students took part in the competition. It appears that the participants dug up information, conducted interviews with sources, namely parents in the villages, then wrote down the results of their studies and pictures of traditional medicinal ingredients.  From the results of the competition, a scientific seminar was held with the theme; Traditional Medicine of the NTT Community; Chemical Content and Activity. The top four competition participants were selected as presenters, and discussed by Natural Materials Chemistry experts in the scientific seminar forum. It was concluded that through research competitions and seminars, it had become a means to train female students to carry out scientific research in their living environment, related to traditional medicine and present their research work.